Mice Lacking Brinp2 or Brinp3, or Both, Exhibit Behaviors Consistent with Neurodevelopmental Disorders - Berkowicz, Susan R.; Featherby, Travis J.; Whisstock, James C.; Bird, Phillip I. (Frontiers in Behavioral Neuroscience, 2016)
Background: Brinps 1 – 3, and Astrotactins (Astn) 1 and 2, are members of the Membrane Attack Complex / Perforin (MACPF) superfamily that are predominantly expressed in the mammalian brain during development. Genetic variation at the human BRINP2/ASTN1 and BRINP1/ASTN2 loci has been implicated in neurodevelopmental disorders. We, and others, have previously shown that Brinp1-/- mice exhibit behaviour reminiscent of autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD). Method: We created Brinp2-/- mice and Brinp3-/- mice via the Cre-mediated LoxP system to investigate the effect of gene deletion on anatomy and behaviour. Additionally, Brinp2-/-Brinp3-/- double knock-out mice were generated by interbreeding Brinp2-/- and Brinp3-/- mice. Genomic validation was carried out for each knock-out line, followed by histological, weight and behavioural examination. Brinp1-/-Brinp2-/-Brinp3-/- triple knock-out mice were also generated by crossing Brinp2/3 double knock-out mice with previously generated Brinp1-/- mice, and examined by weight and histological analysis. Results: Brinp2-/- and Brinp3-/- mice differ in their behaviour: Brinp2-/- mice are hyperactive, whereas Brinp3-/- mice exhibit marked changes in anxiety-response on the elevated plus maze. Brinp3-/- mice also show evidence of altered sociability. Both Brinp2-/- and Brinp3-/- mice have normal short-term memory, olfactory responses, pre-pulse inhibition and motor learning. The double knock-out mice show behaviours of Brinp2-/- and Brinp3-/- mice, without evidence of new or exacerbated phenotypes. Conclusion: Brinp3 is important in moderation of anxiety, with potential relevance to anxiety disorders. Brinp2 dysfunction resulting in hyperactivity may be relevant to the association of ADHD with chromosome locus 1q25.2. Brinp2-/- and Brinp3-/- genes do not compensate in the mammalian brain and likely have distinct molecular or cell-type specific functions.